Contribution to the study of Indigo in Ancient Peru - Velasquez, Manuel A. (1919)
The indigo has been known and used by man over five thousand years ago; Latin is used in dry cleaning, before the discovery of these lands for CRISTOBAL COLON, as evidenced by the countless fabrics dyed with this dye matter which have been exhumed from ancient tombs. According to the testimony of Don Fernando Colon, Cristobal Colon found on the Spanish island of indigo plant and ratifies HERRERA when he says that the "Spanish Island cogefe much. ... anir on stone." The plant you saw is the discoverer of America according Colmeiro the lndigofera dominguensis Spr.